Penggunaan Teknologi dalam Pengelolaan SDM dari Mitra Driver Gojek - Dian Kurnianingrum; Tjutju Yuniarsih; Hady Siti Hadijah (Institut Transportasi dan Logistik Trisakti, 2021)
Gojek is one of the phenomenal transportation start-ups that use technology in most of its business activities. In managing many driver-partners, Gojek uses technology assistance, especially in carrying out recruitments, training, self-development, performance appraisal, and compensation. The use of technology in HR management from driver-partners has a positive impact and negative impact. The purpose of this research is to find the strengths, weaknesses, and problems that arise from the use of technology in managing the HR functions of Gojek driver-partners. This research used qualitative research methods. Researchers used a literature study to examine the use of technology in HR management from Gojek driver-partners and its problems. The use of technology lowers costs and increases efficiency. But it also causes several problems. It is hoped that this research can help companies and governments find an accurate solution for all parties. Other researchers can also use this research as the basis for further study.